Hydrogen Sulfide Increases Nitric Oxide Production from Endothelial Cells by an Akt-Dependent Mechanism - Cardounel, Arturo J.; Julian, David; Predmore, Benjamin L. (Frontiers in Physiology, 2011)
Hydrogen sulfide (H2S) and nitric oxide (NO) are both gasotransmitters that can elicit synergistic vasodilatory responses in the in the cardiovascular system, but the mechanisms behind this synergy are unclear. In the current study we investigated the molecular mechanisms through which H2S regulates endothelial NO production. Initial studies were performed to establish the temporal and dose-dependent effects of H2S on NO generation using EPR spin trapping techniques. H2S stimulated a two-fold increase in NO production from endothelial nitric oxide synthase (eNOS), which was maximal 30 min after exposure to 25-150 µM H2S. Following 30 min H2S exposure, eNOS phosphorylation at Ser 1177 was significantly increased compared to control, consistent with eNOS activation. Pharmacological inhibition of Akt, the kinase responsible for Ser 1177 phosphorylation, attenuated the stimulatory effect of H2S on NO production. Taken together, these data demonstrate that H2S up-regulates NO production from eNOS through an Akt-dependent mechanism. These results implicate H2S in the regulation of NO in endothelial cells, and suggest that deficiencies in H2S signaling can directly impact processes regulated by NO.